2011
DOI: 10.1029/2011gl049163
|View full text |Cite
|
Sign up to set email alerts
|

Rapid settlement of Majuro Atoll, central Pacific, following its emergence at 2000 years CalBP

Abstract: Atoll islands are areas of low, flat land, and the sustainability of habitable land in such environments is sensitive to even slight changes in sea level. The projected rise in sea level during this century may lead to the submergence of atoll islands and the widespread loss of habitable land. However, the actual time sequence of past sea level change, island emergence events, and human settlement of newly emerged islands remain poorly constrained. The results of geomorphological and archaeological surveys, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 20 publications
5
45
1
1
Order By: Relevance
“…In some studies islands have clearly formed on emergent reef fl ats (Woodroffe et al, 1999;Kayanne et al, 2011;Kench et al, 2012) and contemporary reef surfaces (Kench et al, in press) in the midto late Holocene. In the Maldives, however, evidence suggests that some islands formed directly over sediment-infi lled velu rather than over established reef fl ats (Kench et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies islands have clearly formed on emergent reef fl ats (Woodroffe et al, 1999;Kayanne et al, 2011;Kench et al, 2012) and contemporary reef surfaces (Kench et al, in press) in the midto late Holocene. In the Maldives, however, evidence suggests that some islands formed directly over sediment-infi lled velu rather than over established reef fl ats (Kench et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In 1993, Weisler established a research program in the RMI with an aim to consider the regional variation in the archaeology of the archipelago as it correlates with the north-south rainfall gradient (Christensen and Weisler 2013;Pregill and Weisler 2007;Weisler , b, 2001aWeisler , b, c, 2002. The earliest time that atolls in the RMI could have been inhabitable is by ~2000 cal BP (Dickinson 2003;Kayanne et al 2011;, which is in agreement with the earliest human colonisation dates for the archipelago (Kayanne et al 2011;Weisler et al 2012, in prep). Ebon Atoll at the southernmost extent of the archipelago is comprised of 22 islets with a total land area of 5.75 km 2 , which encircles a 104 km 2 lagoon and 22 km 2 reef platform.…”
Section: Chapter 1: Introductionsupporting
confidence: 65%
“…Similar to the general chronology of atoll emergence for the RMI (Dickinson 2003;Kayanne et al 2011;, 2000 BP appears to be the earliest date Marshall Islands atolls were inhabitablealthough some reef islands are appreciably older (Kench et al 2014)-and this matches closely with the earliest human colonization dates for Utrōk Atoll , Majuro Atoll (Kayanne et al 2011), Maloelap Atoll (Weisler 1999a: 640;Weisler et al 2012: 117), and Ebon Atoll (Weisler et al in prep).…”
Section: Sites and Samplessupporting
confidence: 49%
“…Subsequent work in the archipelago has increased archaeological understanding of the lifeways of people living on atolls during the precontract period Harris and Weisler in press-a, b;Horrocks and Weisler 2006;Lambrides and Weisler in press;Pregill and Weisler 2007;Sommerville-Ryan 1998;Weisler , b, 2000Weisler , 2001aWeisler , b, 2002Weisler et al in prep.;). Archaeological analyses have demonstrated that molluscs were a consistent component of subsistence systems in the Marshall Islands from the time of initial colonisation soon after atoll emergence (Kayanne et al 2011;Weisler 1999bWeisler , 2001b. However, these faunae have received little in-depth analysis in the archaeological discourses of the archipelago.…”
Section: Introductionmentioning
confidence: 99%
“…Consisting primarily of unconsolidated sand and gravel atop a narrow reef platform surrounding a lagoon, low coral atolls are challenging landscapes for sustained human habitation; yet the atoll archipelago of the Marshall Islands has been occupied by humans for at least 2000 years (Kayanne et al 2011;Weisler , 2001b. The intertidal zone of atolls is a complex mosaic of benthic habitats that host a diverse range of flora and fauna exploited for subsistence by prehistoric and present day Marshallese.…”
Section: Introductionmentioning
confidence: 99%